Competitive markets, corporate firms, and new governance - An ordonomic conceptualization - Ingo Pies; Markus Beckmann; Stefan Hielscher (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2009)
The purpose of this article is to develop an ordonomic conceptualization of corporate citizenship and new governance that (a) provides a framework for positively explaining the political participation of companies in new governance processes and (b) does not weaken but instead strengthens the functional role of corporations as economic actors in the market system of value creation. To this end, we develop our ordonomic approach in a critical discussion of Milton Friedman's stance on the social responsibility of business in three steps. (1) The ordonomic perspective on the economics ethics of competitive markets argues that the social responsibility of business does not lie in maximizing profits but in addressing societal needs through the mutually advantageous creation of value. (2) The ordonomic approach to the business ethics of corporate actors claims that corporate firms can use moral commitments as a factor of production. (3) The ordonomic perspective on the process ethics of new governance holds that companies can act not only as economic actors but also participate as political and moral actors by taking ordo-responsibility in processes of new governance. This role of corporate citizens in the new governance does not weaken but, instead, strengthens the role of business firms as economic agents for value creation. – – Dieser Beitrag entwickelt eine ordonomische Konzeptualisierung von ,,Corporate Citizenship“ und ,,New Governance“, die (a) ein positives Erklärungsschema bietet für die politische Partizipation von Unternehmen an New-Governance-Prozessen und die (b) zugleich die gesellschaftliche Funktion von Unternehmen als wirtschaftlichen Akteuren im System marktlicher Wertschöpfung nicht schwächt, sondern sogar prononciert. Dieses Argument wird in einer kritischen Diskussion von Milton Friedmans Position zur gesellschaftlichen Verantwortung von Unternehmen in drei Schritten entwickelt. (1) Die ordonomische Wirtschaftsethik wettbewerblich verfasster Märkte macht geltend, dass die gesellschaftliche Verantwortung von Unternehmen nicht darin besteht, ihre Gewinne zu maximieren, sondern darin, gesellschaftliche Probleme durch wechselseitige vorteilhafte Wertschöpfung zu adressieren. (2) Die ordonomische Unternehmensethik korporativer Akteure argumentiert, dass Unternehmen für ihre Wertschöpfung Moral als Produktionsfaktor einsetzen können und müssen. (3) Die ordonomische Prozessethik für den Bereich der New Governance thematisiert, dass Unternehmen nicht nur als wirtschaftliche Akteure, sondern auch als moralische und politische Akteure handeln können, indem sie in New-Governance-Prozessen Ordnungsverantwortung übernehmen. Dieses Verständnis von Corporate Citizenship läuft nicht darauf hinaus, die wirtschaftliche Funktion von Unternehmen zu schwächen, sondern prononciert vielmehr die gesellschaftliche Funktion von Unternehmen als Wertschöpfungsagenten.
urn:nbn:de:gbv:3:2-8953
Keywords: A12; D02; D63; M14; 330; New Governance; Corporate Citizenship; Value Creation; Economic Ethics; Business Ethics; Process Ethics; Ordonomics; Stakeholder Theory; Sustainability; Aristotle; Milton Friedman; Corporate Social Responsibility; New Governance; Corporate Citizenship; Wertschöpfung; Wirtschaftsethik; Unternehmensethik; Prozessethik; Ordonomik; Stakeholder-Theorie; Nachhaltigkeit; Aristoteles; Milton Friedman; Corporate Social Responsibility